2022
DOI: 10.17582/journal.pjz/20190414180419
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Three Silkworm Races Fed on Local Mulberry against Biological and Commercial Parameters

Abstract: Authors' Contribution SZ conducted research work. MH conceived idea, supervised the research work, wrote the manuscript and performed data analysis. KA helped in the write up. MFM helped in improving the manuscript and data analysis. RK provided silk seed and technical support. SL and MK helped in silkworm rearing and data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sabhat et al (2011) evaluated that the larval growth rate, weight and survival rate were greatly affected by ecological factors, quality of leaf and rate of food consumption. However, Zulfiqar et al (2022) recorded better growth in the Bulgarian race as compared to Chinese and Korean races reared in the local climatic conditions of Gujrat Pakistan. They performed their study in the spring season on newly sprouting mulberry leaves whereas our study was conducted in the autumn season on comparatively matured and less succulent leaves.…”
Section: Estimation Of Economic Traitsmentioning
confidence: 83%
See 2 more Smart Citations
“…Sabhat et al (2011) evaluated that the larval growth rate, weight and survival rate were greatly affected by ecological factors, quality of leaf and rate of food consumption. However, Zulfiqar et al (2022) recorded better growth in the Bulgarian race as compared to Chinese and Korean races reared in the local climatic conditions of Gujrat Pakistan. They performed their study in the spring season on newly sprouting mulberry leaves whereas our study was conducted in the autumn season on comparatively matured and less succulent leaves.…”
Section: Estimation Of Economic Traitsmentioning
confidence: 83%
“…According, to our results Chinese race has the potential to perform well when fed with the local mulberry variety (M. alba) in local climatic conditions of Lahore and shows better performance almost in all biological and economic parameters as compared to the other two races. On the other hand, Zulfiqar et al (2022) reported that in the spring season bivoltine Bulgarian race showed better results as compared to Chinese and Korean races for biological and commercial parameters when fed with local mulberry leaves in local climatic conditions of Gujrat Pakistan, while they did not mention the type of local mulberry.…”
Section: Estimation Of Economic Traitsmentioning
confidence: 96%
See 1 more Smart Citation
“…The silkworm ( B. mori ) eggs of Bulgaria Race (Hybrid) were obtained from the Sericulture Wing; Forestry, Wildlife and Fisheries Department, Lahore. Silkworm eggs were incubated under standard light (12 h light: 12 h dark), optimum temperature (25–28 °C) and humidity (70–75 %) for 8 days in the Research Laboratory of Sericulture Wing; Forestry, Wildlife and Fisheries Department, Lahore (31° 36′ 28″ N, 74° 18′ 11″ E) [ [ [28] , [29] , [30] , [31] , [32] ]]. The eggs were hatched after 8 days [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the Cocoon weight, ten cocoons were picked randomly from pupated cocoons as described by Zulfiqar et al (2022) [28] , in each of the three replications and each cocoon was weighed in grams using high precision weighing balance described above. The weighed cocoons were then cut longitudinally on the side so that the pupa could be removed and weighed, with a lot of care not to harm the pupa.…”
Section: Assessment Cocoon Quality and Quantitymentioning
confidence: 99%